A theoretical study of methylation and CH/π interactions in DNA intercalation: methylated 1, 10-phenanthroline in adenine–thymine base pairs. Issue 89 (9th September 2016) - Gil, A.; Branchadell, V.; Calhorda, M. J.
Abstract : This work shows that quality is better that quantity to estabilize the intercalation of methylated phen. Abstract : The study of CH/π interactions in DNA model intercalated systems has been carried out with the popular intercalator 1, 10-phenanthroline (phen) and several methyl derivatives, changing number and position, and the adenine–thymine tetramers (AT/TA) where thymine also contains a methyl group. Density Functional Theory (DFT) was used for the calculations, by means of improved functionals including dispersion effects. Our results given by the AIM analysis confirm the existence of these CH/π interactions and the energy decomposition analysis shows a perfect direct correlation between the number of CH/π interactions found and their Δ E int . Moreover, despite the important role of dispersion energy in the systems with more methyl groups, it is not yet enough to compensate the Pauli repulsion term, Δ E Pauli, and the orbital contribution, Δ E orb, and the electrostatic contribution, Δ E elstat, become crucial for the stabilization of the structures in the intercalation process.